Edgewise bending properties of laminated veneer lumber manufactured from low density woods mixed with keruing (Dipterocarpus spp.) veneers - H'ng, Paik San; Md. Tahir, Paridah (2005)
This paper mainly focuses on the effects of the presence of Keruing on the properties of LVL. LVL of 11-ply and 15-ply panels were fabricated by one high density wood, i.e., Keruing (Dipterocarpus spp.) incorporated with either one of the three low density wood; Pulai (Alstonia spp.), Sesendok (Endospermum spp.) and Kekabu Hutan (Bombax spp.). Keruing veneers were arranged as surface layers whereby, core layers fill by the low density wood. Phenol formaldehyde (PF) resin was used as the binder. The samples were subjected to Accelerated Aging Test (AAT) according to modified Voluntary Product Standard PS1-95. The bending properties and percent delamination were determined according to the Japanese Agricultural Standard (JAS) for Structural LVL (1993) before and after the ATT. Result shows that by incorporating low density wood with Keruing veneers, all types of board in both 11-ply and 15-ply LVL panels achieved the minimum requirements for various grades stipulated in the JAS for Structural LVL (1993). 15-ply LVL panels show a better performance compare to those 11-ply LVL. Presence of Keruing veneers, the better is the performance. All panels passed the delamination test. The Kekabu Hutan as a core layer experience the highest delamination, followed by the Pulai and Sesendok (6.43%, 4.56%, 4.00% in 11-ply and 2.40%, 1.52%, 1.28% in 15-ply LVL respectively). Strength reduction has been observed in all LVL panels after the AAT. Generally, the best performances LVL were produced from panels containing Keruing veneers as surface layers and Sesendok veneers as core layer.